FORMULASI BIOFERTILIZER GRANULAR BERBAHAN MIKROBA Trichoderma sp. - Rizky Nur Affandy; Herry Nirwanto; Wiwik Sri Harijani (Plumula : Berkala Ilmiah Agroteknologi, 2019)
Granular formulation of Trichoderma sp. is a fertilizer containing live microorganisms that are given to plants useful in providing nutrients needed in plant growth and as biological agents. This study aims to determine the effect of giving granular formulations of Trichoderma sp. as a biofertilizer in chili plants. This study used a completely randomized design (CRD) with 4 treatments repeated 6 times. This test uses the shelf life of the Granular Trichoderma sp. Formulation. 7 weeks old. The stages of the study included making suspension of Trichoderma sp., making granular formulations of Trichoderma sp., The preparation of the application of granular formulations on chili plants. The results showed that the granular formulation of Trichoderma sp. the compost carrier can act as the most effective biofertilizer in influencing the height, number of leaves, and dry weight in chili plants.